Ab Initio Analysis of Charge Carrier Dynamics in Organic-Inorganic Lead Halide Perovskite Solar Cells. Issue 1776 (2015) - Junkman, Dakota; Vogel, Dayton J.; Han, Yulun; Kilin, Dmitri S.
ABSTRACT: Today's conversion of solar energy into electricity is based on silicon, which is pure, eventually crystalline, and its most efficient transitions are away from solar radiation maximum. The continuous search of efficient photovoltaic materials has recently focused on lead-halide organic-inorganic perovskite materials due to the very flexible, sustainable, and forgiving procedure of their fabrication, which is successful even if the concentrations of precursors, and temperature regimes deviate from optimal values. In addition to simple fabrication, this class of materials provides impressively high efficiency of photovoltaic (PV) cells. Attention to these materials helps to understand the mechanisms of their high efficiencies and to identify other materials with same type of properties. This work presents computational analysis of photo-induced processes in perovskite materials at ambient temperatures.